Drosophila melanogaster homologs of the raf oncogene. - Mark, G.E.; MacIntyre, R.J.; Digan, M.E.; Ambrosio, L.; Perrimon, N. (Molecular and Cellular Biology, 1987)
A murine v-raf probe, representing the kinase domain, was used to identify two unique loci in Drosophila melanogaster DNA. The most closely related to v-raf was mapped by in situ hybridization to position 2F5-6 (Draf-1) on the X chromosome, whereas the other raf-related gene (Draf-2) was found at position 43A2-5 on chromosome 2. The nucleotide and amino acid homologies of Draf-1 to the kinase domain of v-raf are 61 and 65%, respectively. The large amount of a 3.2-kilobase Draf-1 transcript detected in eggs as a maternal message decreases during embryonic development, and significant steady-state levels are observed throughout the remainder of morphogenesis. We speculate that the Draf-1 locus plays an important role in early embryogenesis.